2008
DOI: 10.1111/j.1365-2672.2007.03574.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of InlB and ActA in Listeria monocytogenes in selective and nonselective enrichment broths

Abstract: Aim:  To investigate the effect of selective and nonselective media on the expression of ActA and InlB proteins in Listeria monocytogenes. Methods and Results:  Polyclonal antibodies to InlB and ActA were used in western blotting to determine the effect of selective (BLEB, UVM, and FB) or nonselective (BHI and LB) enrichment broths or hotdog exudates. Of the 13 L. monocytogenes serotypes tested, 11 and 12 serotypes showed a strong InlB expression in brain heart infusion (BHI) and Luria‐Bertani (LB), respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 54 publications
1
45
0
Order By: Relevance
“…It is therefore possible that a low number of ActA molecules, hardly detectable by Western analysis, may exist in the membrane of bacteria growing in BHI medium. This postulate agrees with observations reported by other authors (37). Likewise, the ⌬actA mutant was highly impaired in the ability to promote invasion of epithelial and fibroblast cells when bacteria were grown in IMM, a condition in which a fraction of ActA molecules associates with peptidoglycan.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is therefore possible that a low number of ActA molecules, hardly detectable by Western analysis, may exist in the membrane of bacteria growing in BHI medium. This postulate agrees with observations reported by other authors (37). Likewise, the ⌬actA mutant was highly impaired in the ability to promote invasion of epithelial and fibroblast cells when bacteria were grown in IMM, a condition in which a fraction of ActA molecules associates with peptidoglycan.…”
Section: Discussionsupporting
confidence: 82%
“…However, we also reasoned that varied interactions of ActA with cell wall components could take place when bacteria grow in markedly different environmental conditions such as the cytosol of eukaryotic cells and laboratory media. Of note, several authors have reported the production in laboratory media of multiple ActA-derived breakdown products resulting from cleavage at defined sites (36,37). Considering this fact, we assessed whether the ActA polypeptide identified by proteomics could display a different envelope association compared with ActA molecules present either in the extracellular milieu or in the membrane but not bound to the peptidoglycan.…”
Section: Acta Associates With Peptidoglycan Of Bacteria Growing In MImentioning
confidence: 99%
“…These results revealed that the three selected MAbs reacted more strongly to lineage I isolates than lineage II isolates grown in enrichment cultures, according to methods described in Health Canada's Compendium of Analytical Methods. Unlike previous studies of potential diagnostic surface proteins which reported reduced protein expression under specific conditions (10,11,36,37), the stable expression of LMOf2365_0639 in enrichment culture makes it a suitable candidate biomarker.…”
Section: Discussionmentioning
confidence: 82%
“…Most surface proteins used as targets for antibody-based methods for L. monocytogenes detection are virulence factors regulated by PrfA (15). Although virulence factors are specific to L. monocytogenes, expression of these factors in in vitro culture is highly variable (10,16,17), most likely due to their adapted expression under intracellular conditions (18,19). Antibody-based assays with specificity for L. monocytogenes have been developed (20)(21)(22); however, the antigen targets recognized by these antibodies are unknown and may be shared with other Listeria species and other non-Listeria foodborne bacteria (21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation